2021
DOI: 10.1016/j.ijpddr.2021.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the in vitro susceptibility of various filarial nematodes to emodepside

Abstract: Filariae are vector-borne nematodes responsible for an enormous burden of disease. Human lymphatic filariasis, caused by Wuchereria bancrofti , Brugia malayi, and Brugia timori, and onchocerciasis (caused by Onchocerca volvulus ) are neglected parasitic diseases of major public health significance in tropical regions. To date, therapeutic efforts to eliminate human filariasis have been hampered by the lack of a drug wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 43 publications
(66 reference statements)
0
14
0
Order By: Relevance
“…Emodepside has been described as a potent microfilaricide in several studies ( Kulke et al, 2014b ; Kashyap et al, 2019 ; Hübner et al, 2021 ). In an in vivo study in bovines, emodepside showed potent macrofilaricidal effects against O. ochengi ( Bah et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Emodepside has been described as a potent microfilaricide in several studies ( Kulke et al, 2014b ; Kashyap et al, 2019 ; Hübner et al, 2021 ). In an in vivo study in bovines, emodepside showed potent macrofilaricidal effects against O. ochengi ( Bah et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…are more readily isolated and can survive for prolonged periods of several months, when cultured on LL-CMK2 monolayers [32]. This system, using the cattle parasite, O. gutturosa, has become adopted as the gold-standard in vitro screen to evaluate nematodicidal or anti-Wolbachia drug candidates [33][34][35][36]. However, limitations of the screen are throughput via sourcing infected cattle, mainly within Sub-Saharan Africa, and differential macrofilaricidal susceptibilities between Onchocerca and lymphatic filariae (as determined for drugs such as moxidectin and albendazole) [37][38][39][40].…”
Section: Discussionmentioning
confidence: 99%
“…L. sigmodontis adult female worms were isolated from chronically infected cotton rats (UKB). Three L. sigmodontis female adult worms per condition were cultured in supplemented Minimal Essential Medium (MEM) on a LLCMK2 cell layer, as previously described [ 67 ]. The positive controls consisted of doxycycline at 40, 20, 10 and 5 µM.…”
Section: Methodsmentioning
confidence: 99%